Cognitive decline : strategies for prevention - Fillit, Howard; Butler, Robert N., 1927-2010. (London : Greenwich Medical Media : Distributed by Oxford University Press, 1997)
Cognitive Decline - Strategies for Prevention examines the problems associated with our understanding of the aging brain, whether or not such decline is inevitable and if there are practical steps which can be taken to prevent or minimise cognitive decline in late life. Our knowledge about the prevention of cognitive decline and dementia in old age has grown rapidly in recent years and it is becoming clear that preventive strategies are now viable.
Cognitive Decline - Strategies for Prevention brings together a group of leading researchers in cognitive aging to assess and make practical recommendations about the strategies currently available. The chapters assess how "normal" cognitive aging should be defined and what the genetic, medical, psychological and environmental factors are which can adversely affect optimal cognitive function in late life. It then goes on to examine how "healthy living" strategies can be employed throughout life to prevent cognitive decline in later years and what are the current research strategies which promise new approaches to prevention in the future
The clinical significance of normal cognitive decline in late life -- Normal cognitive development in adulthood -- Lifestyle risk factors for cognitive impairment -- Education and depression as risk factors for cognitive decline -- Physical activity and cognitive function in old age -- Vascular factors in cognitive decline -- Neuroendocrine factors -- Delirium and cognitive decline -- Intervening in age-related cognitive decline in late life -- Policy and research implications.
Based on a symposium sponsored by the International Longevity Center (ILC-US), the Mount Sinai Medical Center, New York.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Cognition in old age; Cognition disorders in old age -- Prevention; Cognition; Older people; Cognition; Cognition Disorders -- prevention & control; Aging -- physiology; Aged; Cognition chez la personne âgée.; Cognition; Personnes âgées.; cognition; elderly; MEDICAL -- Geriatrics; MEDICAL -- Nursing -- Gerontology; Older people; Cognition; Cognition disorders in old age -- Prevention; Cognition in old age